MANAGEMEN CLEANLINESS THE REGION BANGKINANG CITY KAMPAR (STUDY ABOUT MUNICIPAL WASTE) - Kurniawan Resandi; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
There are several problems about waste management that is the number of piles of household garbage in the temporary disposal place (TPS) and also the rubbish pieces of tree branches near the TPS that is not transported by the worker of the Office of Environment Affair, as well as the street cleaning personnel often throw the garbage into a ditch, this caused frequent floods every time the rain take placed in Bangkinang City. The purpose of this study is to find out how the waste management and what factors affect the governance of the waste management on the region Bangkinang City Kampar regency.The concept of theory used is the theory of management by Goerge R.Terry which starts from planning, organizing, directing and supervision. This research uses qualitative descriptive research method. The type of data used is primary data and secondary data. In the data collecting the writer used observation techniques, interviews, literature study and documentation. Interviews were conducted with key informants, namely the Head of Waste Management, Head of Subdivision of General Affair and Personnel, Section Head of Waste Management, Waste Management Officer, TPAS Supervisor and some other informants. This research use the principle of qualitative analysis, triangulation of data by conducting check and recheck process between one informant and the other informant.The results of this study yielded the conclusion that the governance of waste management in Bangkinang City has not been implemented properly. There are still major lacks in planning, direction and supervision. Then also has been concluded that the factors that affect the governance of waste management in Bangkinang City that is population growth, knowledge and community participation, human resources, facilities and infrastructure, funds/budget.Keyword: management, cleanliness region.